The Impact of Real-Time Feedback on Optimizing Teachers’ Classroom Teaching Pace - Jamal O. Al-Mansouri (Research and Advances in Education, 2024)
Optimizing teaching pace is vital for effective instruction, influencing student engagement and learning outcomes. This paper examines the role of real-time feedback in refining instructional pacing, utilizing tools like natural language processing and interactive technologies to provide immediate, actionable insights. These insights enhance teaching effectiveness and classroom management. Real-time feedback offers psychological and pedagogical benefits. It reduces teacher anxiety, boosts confidence, and fosters a growth mindset, enabling quick adaptation to classroom dynamics. Pedagogically, it encourages a student-centered approach, integrating immediate student feedback to enhance engagement and collaboration. The paper highlights real-time feedback’s transformative potential in creating responsive and adaptive learning environments.